Change of Spontaneous Reaction of Glue and Lipiodol Mixture during Embolization after the Addition of Tungsten Powder: In Vitro Study - Suh, Dae Chul; Shi, Hae Bin; Park, Sang Soo; Lee, Min Suk; Choi, Hye Young (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: We have noted that glue-Lipiodol mixtures harden prematurely in the catheter during embolization of brain arteriovenous malformations. However, we observed that hardening of this embolic material does not occur when tungsten powder is added to the glue mixture. In order to clarify the effect of tungsten powder on the glue mixture, we evaluated the reaction time and hardness of the glue mixture in vitro after the addition of tungsten powder. We also measured the pH of the tungsten solution.METHODS: Six lots of Lipiodol and three lots of Histoacryl Blue were mixed in a 5-cc bottle with a 50% to 25% glue concentration (glue:Lipiodol = 1:1 to 1:3) and this mixture was observed for 2 weeks. The hardness of the polymerized glue mixture was categorized as liquid, gel, semi-solid, or solid. Various series of experiments were performed after the addition of tungsten powder (0.2 g) and blood (a drop) into the glue mixture. We also separately mixed tungsten and tantalum powder in tubes, each with 5 mL of distilled water, and then measured the pH of these three times. The mixed amounts of tungsten and tantalum ranged from 0.1 to 0.5 mg.RESULTS: In a 50% glue concentration, the glue mixture turned into a solid cast within 48 hours. In a 25% concentration, the glue mixture turned into gel within 24 hours. The casts became solid in the 50% and gelled in the 25% concentration, and solid or gel in 28% and 33% glue mixture concentrations. The addition of tungsten powder to 50% and 25% glue mixture concentrations caused the glue mixtures to remain in a liquid state for 2 weeks regardless of the Lipiodol products used. Measurement of acidity achieved using a pH meter in 5 cc of distilled water with tungsten powder (0.1 to 0.5 g) revealed a change of pH from 3.5 to 2.6 according to the amount of tungsten added. Tantalum revealed weak acidity, with a pH range from 6.4 to 5.7. The addition of blood immediately caused the mixture to become solid in 50% and semi-solid in 25% glue concentrations.CONCLUSION: The reaction time of the glue mixture differed according to the lot number of the Lipiodol. The addition of tungsten powder appeared to prevent premature cast formation by decreasing the pH with a mechanism similar to that of adding acetic acid.